Employee Participation Plans in the U.S.: How Far Can They Go? - Perline, Martin; Poynter, David (Relations industrielles / Industrial Relations, 1991)
In order to deal with the intense competition, both from international and domestic sources, there has been a movement among unions and management in the U.S. to forge a new cooperative relationship. While the notion of cooperation has taken numerous forms, one such approach involves labor participation in some phase of the production process through various programs. Their progress up the hierarchy is such that they are more likely to step on traditional managerial prerogatives. Does this lead management to re-evaluate its position on these prerogatives?